Overexpression of miR-191 Predicts Poor Prognosis and Promotes Proliferation and Invasion in Esophageal Squamous Cell Carcinoma - Gao, Xiaotian (Yonsei Med J, 2017)
PURPOSE: Accumulating evidence has shown that dysregulation of microRNA-191 (miR-191) is closely associated with tumorigenesis and progression in a wide range of cancers. This study aimed to explore the potential role of miR-191 in esophageal squamous cell carcinoma (ESCC). MATERIALS AND METHODS: miR-191 expression was assessed in 93 ESCC tissue specimens by real-time polymerase chain reaction, and survival analysis was performed via Kaplan-Meier and Cox regression analyses. 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide, plate colony-forming, BrdU, and Transwell assays were conducted to observe the effect of miR-191 on ESCC proliferation and invasion. Luciferase reporter and western blot assays were taken to identify target genes of miR-191. RESULTS: miR-191 was overexpressed in 93 cases of ESCC, compared with adjacent normal tissues, and miR-191 expression was significantly related to differentiation, depth of invasion, TNM stage, lymph node metastasis, and distant metastasis of tumor. Kaplan-Meier and Cox regression analyses demonstrated that overexpression of miR-191 was an independent and significant predictor of ESCC prognosis. Both gain-of-function and loss-of-function experiments showed that miR-191 promoted ESCC cell proliferation and invasion activities in vitro. Early growth response 1 (EGR1), a tumor suppressor, was predicted as a direct target of miR-191. Luciferase reporter and western blot assays proved that miR-191 reduced EGR1 expression by directly binding its 3' untranslated region. Moreover, EGR1 knockdown by siRNA enhanced ESCC cell growth and invasion. CONCLUSION: Our findings provide specific biological roles of miR-191 in ESCC survival and progression. Targeting the novel miR-191/EGR1 axis represents a potential new therapeutic way to block ESCC development.